1994
DOI: 10.3354/meps107169
|View full text |Cite
|
Sign up to set email alerts
|

Sulphide 'mining' by lucinid bivalve molluscs: demonstrated by stable sulphur isotope measurements and experimental models

Abstract: A profile of the isotopic composition 634S, of elemental sulphur, acid-lablle sulphide, chromous-reducible sulphide and dissolved sulphate was recorded from 30 cm long cores taken from a sandy sedlrnent at the low water mark at Mlll Bay, a beach near the mouth of the Salcombe Estuary SW England The sediment is inhabited by the bivalve mollusc Luanoma boreahs, which has concentrations of elemental sulphur within endosymbiotic sulphur-oxidising bactena in the gills Sulphur from the g~l l s was more depleted in 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Rau 1981, MacAvoy et al 2002. It may occur via symbiotic relationships, such as those between lucinid bivalves or marine nematodes and sulphur-oxidising bacteria, in sub-oxic, anoxic and sulphidic benthic habitats (Spiro et al 1986, Dando et al 1994, Ott et al 2004. Multiple trophic resources for marine chemoautotrophic communities have been demonstrated using multiple stable isotopes (Brooks et al 1987, Cary et al 1989) but comparatively little work has been conducted regarding the importance of these alternative trophic pathways in freshwater systems.…”
Section: Discussionmentioning
confidence: 99%
“…Rau 1981, MacAvoy et al 2002. It may occur via symbiotic relationships, such as those between lucinid bivalves or marine nematodes and sulphur-oxidising bacteria, in sub-oxic, anoxic and sulphidic benthic habitats (Spiro et al 1986, Dando et al 1994, Ott et al 2004. Multiple trophic resources for marine chemoautotrophic communities have been demonstrated using multiple stable isotopes (Brooks et al 1987, Cary et al 1989) but comparatively little work has been conducted regarding the importance of these alternative trophic pathways in freshwater systems.…”
Section: Discussionmentioning
confidence: 99%
“…The species Thyasira sarsi and Lucinoma borealis can also utilize insoluble sulphur species (such as iron-bound sulphides; Dando et al 1994Dando et al , 2004. The concentration of insoluble sulphur compounds in marine sediments depends on microbial sulphate reduction rates and on the density of the exploiting bivalves (Dando et al 2004); as for dissolved sulphide, their concentration can vary seasonally and yearly (Dando et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, such burrows are limited to a maximum depth of 30 脳 the shell length, which would be 255 mm in the pre- sent study, and free sulphide was still undetectable at 500 mm depth in our sediment samples. This suggested that, as described for Lucinoma borealis (Dando et al 1994b), T. sarsi are able to 'mine' the insoluble sulphur species in the sediment by drawing oxygenated water through a semi-permeable inhalant tube. .…”
Section: Discussionmentioning
confidence: 99%
“…As with other lucinaceans (Dando et al 1994b), pumping oxygenated water through the semi-permeable inhalant tube results in rapid oxidation of the iron sulphides in the surrounding sediment. Disproportionation of the thiosulphate that is formed under these conditions results in free sulphide becoming available and diffusing back into the tube.…”
Section: Discussionmentioning
confidence: 99%